Sol-Gel Cupric Oxide Thin Film Transistors: Alkali Metal Doping for Low Temperature Flexible Devices - Baek, Seokhyeon; Na, Jeongyeon; Kim, Wonsik; Hwang, Chuljin; Park, Sungjun (IFETC 2023 - 5th IEEE International Flexible Electronics Technology Conference, Proceedings, 2023)
Solution-processed copper oxide (CuxO) semiconductors have gained significant interest in recent years due to their p-Type conductivity, transparency, nontoxicity, and low cost. However, the development of CuxO thin film transistors (TFTs) has been limited by their low field-effect mobility and poor reproducibility. In this study, we present a simple solution doping process for producing high-performance sol-gel-based CuO TFTs under ambient conditions. By doping the precursor solution with an alkali metal, we achieved a more than 10-fold increase in device mobility compared to pristine CuO transistors annealed at the same temperature. These results suggest the possibility of implementing solution processed p-Type oxide transistors at lower temperatures, thereby enabling CuO TFTs to be realized on flexible plastic substrates.
Keywords: Alkali metal doping; C. thin film transistor (TFT); CuO thin films; Flexible device; Lows-temperatures; P type conductivity; P-type oxides; Sol'gel; Solution process; Solution-processed; alkali metal; copper oxide; doping; p-Type oxide; solution process; thin film transistors